Blucher Design Proceedings 2020
DOI: 10.5151/eneac2020-96
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação ergonômica do ambiente construído: estudo de caso da Universidade Integrada da Terceira Idade – UNITI/UFMA

Abstract: In the last two decades Universities, Federal Institutes and private institutions have intensified the process of interiorizing their campi (hitherto predominantly located in capitals), which has led to an accelerated construction of new buildings. Given the speed of the phenomenon, among other factors, many of these educational centers were opened without due attention to ergonomic factors, generating buildings that are inadequate from a human point of view, due to the standardization of projects. Thus, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The first sub-theme concerns the experiences of women, who admitted that retirement was not meeting their expectations. They reported a predominance of negative experiences at this stage, connected with ageism [i.e., age-based negative attitudes; e.g., [14] and the respective negative representation of age that predominates in our society. However, we can also perceive some positive experiences reported by these women, who highlighted the time spent with their grandchildren: Retirement always scared me because it was significant of old age.…”
Section: Gendered Experiences Of Retirementmentioning
confidence: 99%
See 1 more Smart Citation
“…The first sub-theme concerns the experiences of women, who admitted that retirement was not meeting their expectations. They reported a predominance of negative experiences at this stage, connected with ageism [i.e., age-based negative attitudes; e.g., [14] and the respective negative representation of age that predominates in our society. However, we can also perceive some positive experiences reported by these women, who highlighted the time spent with their grandchildren: Retirement always scared me because it was significant of old age.…”
Section: Gendered Experiences Of Retirementmentioning
confidence: 99%
“…Finally, studying this topic will also help to demystify the mistaken beliefs that exist in relation to this stage of life, which is still neglected and considered one of the least interesting stages of human life [4], since the lack of knowledge about the process of growing old leads to negative attitudes towards it [12]. A growing body of authors has demonstrated how older people are a target of ageism, i.e., negative attitudes and practices based on the age of individuals, e.g., [13,14].…”
Section: Introductionmentioning
confidence: 99%